Respon Perbankan Syariah di Indonesia Terhadap Bauran Kebijakan Bank Sentral - Nurul Azizah Az zakiyyah; Arief Mulyawan (Muttaqien, 2025)
Indonesia adheres to a dual banking system and a dual monetary system which causes conventional and Islamic banking to operate together. On the other hand, various central bank policies, including fiscal, monetary, portfolio management, and macroprudential policies, are still dominated by the conventional basis, which poses a challenge for sharia banking. This study aims to analyze how Islamic banking responds to various shocks or shocks caused by the policy mix. The method used in this research is VECM analysis accompanied by Impulse Response Function (IRF) and Variance Decomposition (VD). The period used starts in 2012 Q1 to 2021 Q4. The independent variables used are Government Total Expenditure (GEXP), Policy Interest Rate (PIR), Broad Money (M2), Investment Portfolio (PI), Sharia Macroprudential Intermediation Ratio (RIM), and Consumer Price Index (CPI). In contrast, the dependent variable is Total Islamic Banking Assets (TAPS). The results show that PIR, M2, and CPI have a negative response, while GEXP, PI, GDP, and RIM respond positively